सिन्धुपाल्चोक जिल्लामा प्रचलित असारे गीतमा प्रगतिशीलता (Asare Songs prevalent in Sindhupalchok District) - Bishwokarma, Bipen (International Research Journal of MMC, 2025)
सिन्धुपाल्चोक जिल्लामा प्रचलित असारे गीतमा प्रगतिशीलताको खोजी गर्नु यस अध्ययनको मुख्य विषय हो । यसै सन्दर्भमा सिन्धुपाल्चोक जिल्लामा प्रचलित असारे गीतमा के कस्तो प्रगतिशील चेत कसरी प्रयोग भएको पाइन्छ भन्ने मूल समस्याको समाधान गर्ने उद्देश्य यसमा रहेको छ । यसमा निगमनात्मक विधिको उपयोग गरिनुका साथै पाठविश्लेषण पद्धतिको प्रयोग गरी गीतको अध्ययन गरिएको छ । क्षेत्रीय भ्रमणबाट प्राथमिक स्रोत सामग्री र पुस्तकालयबाट द्वितीयक स्रोत सामग्रीको सङ्कलन गरिएको छ । यहाँ प्रगतिवादी सिद्धान्तबाट सैद्धान्तिक आधार तय गरिएको छ । यसै सैद्धान्तिक अवधारणको आलोकमा वर्गीय उत्पीडनको प्रस्तुति, जातीय तथा लैङ्गिक विभेदको प्रस्तुति, पितृसत्तावादले निम्त्याएको समस्याको उजागर, सामाजिक तथा संस्कृतिक पहिचानको खोजी, प्रकृति र श्रमप्रति सम्मान भाव प्रकट र सङ्घर्षको निरन्तरता, मानवीय जीवनलाई खुसी र सुखी बनाउने चाह प्रकट गरी यी छओटा आधार तय गरी सिन्धुपाल्चोक जिल्लामा प्रचलित असारे गीतको विश्लेषण गरिएको छ । उक्त विश्लेषणका आधारमा सिन्धुपाल्चोक जिल्लाको लोकसमाजमा गाइने असारे गीतमा प्रगतिशीलचेत सशक्त रहेको निष्कर्ष निकालिएको छ । [The Main subject of this study is to explore the progressiveness in the Asare songs prevalent in Sindhupalchok district. In this context the main objective of this study is to address the central problem of how and what kinds of progressive consciousness are reflected in the Asare songs prevalent in Sindhupalchok district. Along with the use of the deductive method, the study has been conducted by applying the text analysis (meta) approach. Primary source materials have been collected through field visits and secondary Source Materials have been gathered from the library. Here the theoretical Framework has been developed based on the progressive theory. In the light of this theoretical concept six bases have been developed to analyze the Asare songs prevalent in Sindhupalchok district. These include: the representation of class oppression, they depiction of ethnic and gender discrimination, the exposure of problems caused by patriarchy, the search for social and cultural identity, the expression of respect toward nature and labor and the revelation of continuous struggle along with the desire to make human life happy and prosperous .Based on this analysis, it has Been concluded that the Asare songs sung in the folk society of Sindhupalchok district contain a strong Sense of progressive consciousness.]